Crises in The Global Economy from Tulips to Today: Contagion and Consequences - Larry Neal; Marc D. Weidenmier (Claremont McKenna College, Department of Economics, 2001)
We examine the historical record of the financial crises that have often accompanied surges of globalization in the past. The issue of contagion, the spread of financial turbulence from the crisis center to its trading partners, is confronted with historical and statistical evidence on the causes and consequences of well-known crises. Special attention is given to the gold standard period of 1880-1913, which we find useful to divide into the initial period of deflation, 1880-1896, and the following period of mild inflation, 1897-1913. We find evidence of changes in the pattern of 'contagion' from core to periphery countries between the two periods, finding that apparent contagions can more readily be interpreted as responses to common shocks. Lessons for the present period can only be tentative, but the similarities in learning experiences are striking.
Keywords: 330; contagion; gold standard